Analisis Kecukupan Modal di Sistem Perbankan Indonesia - KHAIRANATUNNISSA; Doni satria (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the factors influencing the Capital Adequacy Ratio (CAR) in the Indonesian banking sector. The data used consists of panel data from 22 conventional commercial banks for the period 2017Q1–2025Q4, sourced from financial statements and the Financial Services Authority (OJK). The independent variables include operational efficiency (BOPO), credit risk (NPL), liquidity (LDR), Bank Size, and profitability (ROA). The analysis employs panel data regression using the Fixed Effects Model (FEM) based on the Chow and Hausman tests. The results show that all variables collectively¹ have a significant impact on CAR. BOPO has a negative impact and NPL has a positive impact, while LDR and Bank Size have positive impacts on CAR, and ROA has a negative impact on CAR. These findings highlight the importance of efficiency, risk management, and performance improvement in strengthening capital adequacy and maintaining banking stability.